Cross-language influences in bilingual processing and second language acquisition - Elgort, Irina; Siyanova-Chanturia, Anna; Brysbaert, Marc 1963- (John Benjamins Publishing Company, 2023)
"A great majority of people around the world know more than one language. So, how does knowing one language affect the learning and use of additional languages? The question of cross-language influences is the focus of this book. Do bilinguals hear, understand, and produce language and meaning differently because of the languages they speak? How well can theoretical and computational models of language processing and acquisition explain and predict bilingual use patterns and acquisition trajectories? What learner, language, and context characteristics influence bilingual comprehension and production? This book provides a state-of-the-art review and critique of research into cross-language influences in phonology, lexicon, and morphosyntax, and suggests directions for future research. The interdisciplinary nature of the book bridges the gap between research on bilingualism and second language acquisition. The book will be of interest to graduate students, teachers, and researchers in linguistics and second language acquisition, cognitive psychology, and language education"--
Includes bibliographical references and index
Keywords: Zweisprachigkeit; Kognitive Grammatik; Fremdsprachenlernen; Language transfer (Language learning); Bilingualism; Second language acquisition; Cognitive grammar; Essays; Aufsatzsammlung